Sensitive and selective determination of aqueous triclosan based on gold nanoparticles on polyoxometalate/reduced graphene oxide nanohybrid - Yola, M.; Atar, N.; Eren, T.; Karimi-Maleh, H.; Wang, Shaobin (Royal Society of Chemistry, 2015)
The widespread use of triclosan (TCS) in household cleaning products, medical devices and personal care poses a potential risk to the ecological system and human health due to its release into sediments, surface water and ground water resources and chronicle toxicity to aquatic organisms. A novel molecular-imprinted electrochemical sensor based on gold nanoparticles decorating polyoxometalate (H3PW12O40)/reduced graphene oxide was developed for determination of trace TCS in wastewater. Reduced graphene oxide (rGO) was functionalized by polyoxometalate (POM) through electrostatic interaction between the POM and rGO nanosheets to produce a photocatalyst (POM/rGO) in aqueous solution. Gold nanoparticles (AuNPs) were further deposited on the POM/rGO without using any reducing agent and the prepared nanomaterial (AuNPs/POM/rGO) was employed to modify a glass carbon (GC) electrode (AuNPs/POM/rGO/GC) under infrared light. Several techniques, X-ray photoelectron spectroscopy (XPS), reflection-absorption infrared spectroscopy (RAIRS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), were used for electrode characterization. TCS imprinted film was generated on AuNPs/POM/rGO/GC via polymerization of phenol and TCS and characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The sensor was found to have a linear detection range and a limit of TCS at 0.5–50.0 nM and 0.15 nM, respectively. The molecular imprinted sensor was applied to wastewater and lakewater samples and demonstrated effective performance as compared to other complicated methods.